2011
DOI: 10.1371/journal.pone.0027610
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Anti-Tuberculosis Medication Adverse Effects: A Case-Control Study in Lima, Peru

Abstract: BackgroundLong-term exposure to anti-tuberculosis medication increases risk of adverse drug reactions and toxicity. The objective of this investigation was to determine factors associated with anti-tuberculosis adverse drug reactions in Lima, Peru, with special emphasis on MDR-TB medication, HIV infection, diabetes, age and tobacco use.Methodology and ResultsA case-control study was performed using information from Peruvian TB Programme. A case was defined as having reported an anti-TB adverse drug reaction du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
53
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 26 publications
10
53
2
3
Order By: Relevance
“…This finding is in line with studies conducted elsewhere. 2,15 In contrast to our finding, baseline body weight # 45 kg has been reported as a predictor of ADRs in MDR-TB patients in a study conducted in Namibia. 11 Limited information is available to explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in line with studies conducted elsewhere. 2,15 In contrast to our finding, baseline body weight # 45 kg has been reported as a predictor of ADRs in MDR-TB patients in a study conducted in Namibia. 11 Limited information is available to explain this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…With respect to TB therapy-related adverse events, one study reported a significantly increased risk (OR 2.00) in smokers [122]. In contrast, smoking has been reported to attenuate isoniazid-associated hepatotoxicity by increasing N-acetyltransferase 2 activity, with potential implications for efficacy of therapy [123].…”
Section: Tuberculosismentioning
confidence: 99%
“…Overall, this situation can predispose patients to develop adverse drug reactions due to the long-time exposition to the anti-TB drugs [2] [3].…”
Section: Introductionmentioning
confidence: 99%